1999
DOI: 10.1002/(sici)1099-0682(199908)1999:8<1271::aid-ejic1271>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Predetermined Chirality in Mono- and Dinuclear Cyclometalated Rhodium(III) Complexes

Abstract: Dinuclear and polynuclear metal complexes with octahedral centers coordinated to di‐ or polydentate ligands are often obtained as complicated mixtures of various stereoisomers. Stereospecific synthesis of such species is therefore of high current interest. Chiral derivatives of pyridine can be used for this purpose. Dinuclear μ‐chloro‐bridged RhIII complexes with two didentate, cyclometalated thienylpyridine‐type ligands at each metal center are formed stereoselectively when pinene groups are fused to the pyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This phenomenon has also been observed in bridged dinuclear octahedral complexes using suitable chiral building blocks in the solid state 2a,2b,4. A pronounced diastereoselectivity was reported in dinuclear ΔΔ[Rh(L) 2 (μ‐Cl)] 2 [L = th4,5( R , R )ppy] with ΔΔ/ΛΛ = 9:1 and in ΛΛ[Rh(L′) 2 (μ‐Cl)] 2 [L′ = th4,5( S , S )ppy] with ΛΛ/ΔΔ = 9:1, according to the results of X‐ray studies 17a…”
Section: Introductionmentioning
confidence: 82%
“…This phenomenon has also been observed in bridged dinuclear octahedral complexes using suitable chiral building blocks in the solid state 2a,2b,4. A pronounced diastereoselectivity was reported in dinuclear ΔΔ[Rh(L) 2 (μ‐Cl)] 2 [L = th4,5( R , R )ppy] with ΔΔ/ΛΛ = 9:1 and in ΛΛ[Rh(L′) 2 (μ‐Cl)] 2 [L′ = th4,5( S , S )ppy] with ΛΛ/ΔΔ = 9:1, according to the results of X‐ray studies 17a…”
Section: Introductionmentioning
confidence: 82%
“…The homochiral complexes are energetically favoured by 7.77 kcal/mol at HartreeϪFock level. On the basis of molecular modelling studies of [(ppy) 2 Rh(µ-Cl)] 2 [19] and closely related complexes, [20] it has previously been suggested that the meso form is less stable due to interligand steric repulsion. Accordingly, for this class of compounds only ∆∆/ΛΛ complexes have been structurally characterized.…”
Section: Computational Studymentioning
confidence: 99%
“…Accordingly, for this class of compounds only ∆∆/ΛΛ complexes have been structurally characterized. [20,21] A common feature of all the symmetrical complexes is a planar M(µ-Cl) 2 M unit ( Table 2, Entries 1Ϫ11), the only exception being [(PPh 3 ) 2 Pd(µ-Cl)] 2 2ϩ , which displays a slightly bent chloro bridge in the crystal. This characteristic is also observed for most other halo-bridged complexes of d 8 transition metal ions.…”
Section: Computational Studymentioning
confidence: 99%
“…[16] In Table 2, selected structural data for some of the computed species are compared with the experimental data. On the basis of molecular modelling studies of [(ppy) 2 Rh(µ-Cl)] 2 [19] and closely related complexes, [20] it has previously been suggested that the meso form is less stable due to interligand steric repulsion. For [(H 3 P)MCl(µ-Cl)] 2 (M ϭ Pd, Pt), two different isomers (cis and trans) were obtained.…”
Section: Computational Studymentioning
confidence: 99%
“…The molecular structures of all the species were fully optimized at the B3LYP level and characterized as minima by a frequency analysis. [20,21] A common feature of all the symmetrical complexes is a planar M(µ-Cl) 2 M unit ( Table 2, Entries 1Ϫ11), the only exception being [(PPh 3 ) 2 Pd(µ-Cl)] 2 2ϩ , which displays a slightly bent chloro bridge in the crystal. The trans isomer was found to be stabilized by ca.…”
Section: Computational Studymentioning
confidence: 99%